1982
DOI: 10.1037/0033-2909.91.3.498
|View full text |Cite
|
Sign up to set email alerts
|

Paid employment and women's psychological well-being.

Abstract: Research by psychologists, psychiatrists, and sociologists is examined within a three-component conceptual framework. This suggests that the association between employment status and psychological well-being is mediated by a woman's occupational involvement, the quality of her nonoccupational environment, and (if she has a job) the quality of her employment relationship. These three features are operationalized at the group level and at the individual level to show that in certain circumstances psychological w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
101
1
3

Year Published

1984
1984
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(108 citation statements)
references
References 54 publications
3
101
1
3
Order By: Relevance
“…The possible differential effects of employment on men's and women's positive well-being awaits additional investigation (see Baruch, Biener, & Barnett, 1987, Hirsh & Rapkin, 1986, and Warr & Parry, 1982, for relevant theoretical analyses).…”
Section: Employment Rolementioning
confidence: 99%
“…The possible differential effects of employment on men's and women's positive well-being awaits additional investigation (see Baruch, Biener, & Barnett, 1987, Hirsh & Rapkin, 1986, and Warr & Parry, 1982, for relevant theoretical analyses).…”
Section: Employment Rolementioning
confidence: 99%
“…Other research has found no significant difference in the mental health outcomes between employed and unemployed women. [7,[11][12][13][14][15][16] Repetti et al compared the distress levels of employed and unemployed single and married women, and found that employment was associated with improved mental health for both groups. [17] A more recent study, which used a large, national sample, found that mental well-being was positively related to the mother's employment and negatively related to her total number of children.…”
Section: Employmentmentioning
confidence: 99%
“…That has been reported by Rundquist and Sletto (1936) in terms of 'general adjustment' and 'morale', by Cohn (1978) in respect of satisfaction with self, and by Hep worth (1980) in respect of minor psychiatric morbidity and life satisfaction. Warr and Parry (1982) concluded from their literature review and data analyses that among women in general (amongst whom there is no general correlation between psychological health and employment status) having a job is likely to benefit the psychological health of working-class women but not those in middleclass samples.…”
Section: Introductionmentioning
confidence: 99%